Synthesis and thermal properties of nanocomposites based on exfoliated organoclay polystyrene and poly(methylmethacrylate). Issue 1 (2nd January 2017) - Akelah, Ahmed; Rehab, Ahmed; Abdelwahab, Mohamed; Betiha, Mohamed A.
Abstract: Exfoliated organoclay-polystyrene (OC-PS) and organoclay-poly(methyl methacrylate) (OC-PMMA) nanocomposites were prepared using novel modified/clay-polymer through both bulk polymerization and solution techniques. The synthesis was achieved by formation of derivative vinylbenzyl ammonium salt intercalated with montmorillonite (MMT) clay. The clay-vinyl/monomer was dispersed in PS or MMA monomers followed by solution polymerization. The clay-PS and clay-PMMA were used as highly compatibilizer organoclay to produce highly exfoliated nanocomposites. Morphological structure of the nanocomposites was investigated by SEM and XRD which confirmed that the clay is homogenously dispersed and exfoliated in the polymer matrixes with interlayer spacing at least of d001-value ≥4 nm for both PS and PMMA. Thermal properties of the nanocomposites show an increase in the decomposition temperature comparing to neat polymer. Abstract :